Cutaneous Involvement of Extranodal NK/T Cell Lymphoma, Nasal Type, a Clinical and Histopathological Mimicker of Various Skin Diseases - Preeyawat Ngamdamrongkiat; Sanya Sukpanichnant; Manasmon Chairatchaneeboon; Archrob Khuhapinant; Panitta Sitthinamsuwan (Dermatopathology, 2022)
Background: Extranodal NK/T cell lymphoma, nasal type (ENK/T) with cutaneous involvement has various histopathological findings and diverse clinical manifestations. Methods: A retrospective study of cutaneous involvement of ENK/T lymphoma between 2006 and 2018 was conducted. Results: Twenty-two cases were eligible for this study. Twelve cases could be proven as secondary cutaneous involvement by ENK/T lymphoma, while the remaining could not be confirmed as primary cutaneous ENK/T lymphoma. The histopathological patterns included dermal and subcutaneous nodular infiltration pattern in 11/22 cases (50%), lobular panniculitis pattern in 6/22 cases (27.3%), interface dermatitis pattern in 4/22 cases (18.2%), and granulomatous dermatitis pattern in 1/22 case (4.5%). The median follow-up was 18.3 months. Overall, the one-year and five-year survival rates were 31.3% and 13.3%, respectively. Conclusions: A variety of histopathological patterns of cutaneous involvement by ENK/T lymphoma should be differentiated from other cutaneous lymphomas, dermatitis, and infection. When atypical medium or large-sized lymphoid cells are encountered within skin lesions, pathologists should realize these lesions can be ENK/T lymphoma, especially in cases with coexisting tumor necrosis or angioinvasion. A complete evaluation of the upper aerodigestive tract is mandatory to identify the occult primary site of ENK/T lymphoma before establishing primary cutaneous ENK/T lymphoma.